PENGELOLAAN PESISIR DAN KELAUTAN DALAM STUDI KASUS PENGELOLAAN EKOSISTEM BAKAU DI KOTA PARIAMAN - Hafida Istigfarini; Rahayu Tia Khairani; Fadhilla Oktari; Abdul Razak; Eni Kamal; Widya Prarikeslan; Mhd. Ridha (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
Mangrove ecosystems are an important component of coastal areas that have strategic ecological functions, including acting as natural coastal protection from abrasion, providing habitat and seeds for fisheries, and absorbing carbon that plays a role in mitigating climate change. However, the existence of mangrove ecosystems in various coastal areas of Indonesia, including Pariaman City, faces serious pressure due to human activities and weak coastal area governance. The problem formulation in this study includes the factors causing problems in the mangrove ecosystem in Pariaman City and how the central role of coastal area governance can strengthen the ecological function of mangroves as coastal protection, providing seeds for fisheries, and absorbing carbon. This study aims to analyze the role of management and protection of coastal ecosystems, especially mangrove forests, in the governance of the coastal area of ​​Pariaman City. The research methodology uses a literature review method with a descriptive analysis approach, which examines 15 selected articles. The results of the study indicate partial to significant degradation of mangrove areas due to land conversion, reclamation, logging, and industrial and household pollution. Human pressures such as shrimp pond expansion, coastal infrastructure development, and land reclamation also exacerbate abrasion and reduce the productivity of the mangrove ecosystem. On the other hand, mangroves have significant potential as an instrument for climate change adaptation and mitigation through increasing blue carbon and coastal rehabilitation. Therefore, this study emphasizes the importance of community-based governance policies, mangrove restoration programs, and cross-sector partnerships to maintain the sustainability of Pariaman City's coastal ecosystem.